САЙФ УЗ – ЗАФАР НАВБАХАРИЙДЫҢ ЭТИКАЛЫҚ КӨЗҚАРАСЛАРЫ («ДУРР УЛ- МАЖОЛИС» ШЫҒАРМАСЫ МЫСАЛЫНДА) - Есназарова, З.Б.; Нәўбетуллаева, Э.; Утемисов, А. (FAN va JAMIYAT, 2022)
The article is based on the example of «Pearl of Conversation», which mainly analyzes universal human moral norms, such as conscience, faith, loyalty devotion, modesty piety, philanthropy, compassion, love and kindness.